2014
DOI: 10.1371/journal.pone.0105168
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Regulatory Mechanisms of Activating Transcription Factor 3 by Hypertrophic Stimuli in Rat Cardiomyocytes

Abstract: AimsActivating transcription factor 3 (ATF3) is a stress-activated immediate early gene suggested to have both detrimental and cardioprotective role in the heart. Here we studied the mechanisms of ATF3 activation by hypertrophic stimuli and ATF3 downstream targets in rat cardiomyocytes.Methods and ResultsWhen neonatal rat cardiomyocytes were exposed to endothelin-1 (ET-1, 100 nM) and mechanical stretching in vitro, maximal increase in ATF3 expression occurred at 1 hour. Inhibition of extracellular signal-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Moreover, activated caspase-3 was also detectable from renal tissue at 6 h of CLP by Western blot analysis support the association of apoptosis and ATF3 or NGAL as previously described [33]. Despite ATF3 is not specific to kidney as it was also demonstrated in other organs as previously known [3436], it seems to be activated only in condition with organs injury as there was no ATF3 expression in sham mice. Then ATF3 in urine should be a better representative renal biomarker than serum ATF3.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, activated caspase-3 was also detectable from renal tissue at 6 h of CLP by Western blot analysis support the association of apoptosis and ATF3 or NGAL as previously described [33]. Despite ATF3 is not specific to kidney as it was also demonstrated in other organs as previously known [3436], it seems to be activated only in condition with organs injury as there was no ATF3 expression in sham mice. Then ATF3 in urine should be a better representative renal biomarker than serum ATF3.…”
Section: Discussionsupporting
confidence: 88%
“…) as well as transcription factors involved in cardiac inflammatory response (Koivisto et al. ), but whether mechanical stress functions directly as a proinflammatory stimulus remains to be established. It is noteworthy that although the primary cultures derived from the adult rat heart would reflect better the situation in the adult heart, the limitation is that these cultured cells either lose their morphology or they lose their ability to undergo spontaneous contractions, if cultured under conditions where the rod‐shaped morphology is retained (Jacobson and Piper ; Mitcheson et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mechanical stretch coupled cellular release of Ang II could mediate the increase in Reg3c mRNA levels (Sadoshima et al 1993;Liang and Gardner 1998). Mechanical stretch is also known to induce gene expression of other inflammatory mediators such as IL-18, tumor necrosis factor-like weak inducer of apoptosis (TWEAK) and its receptor Fn14 (Mustonen et al 2010;Yoshida et al 2014) as well as transcription factors involved in cardiac inflammatory response (Koivisto et al 2014), but whether mechanical stress functions directly as a proinflammatory stimulus remains to be established. It is noteworthy that although the primary cultures derived from the adult rat heart would reflect better the situation in the adult heart, the limitation is that these cultured cells either lose their morphology or they lose their ability to undergo spontaneous contractions, if cultured under conditions where the rod-shaped morphology is retained (Jacobson and Piper 1986;Mitcheson et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…ATF3 upregulation under stress was proven to be mediated exclusively by the p38 476 signaling pathway in HeLa cells, while through ERK, SAPK and p38 in colorectal cancer 18,56 . 477 Other reports showed that its activation is mediated through ERK and p38α in myocytes or by 478 ERK/JNK but not by p38 in rat brains 57,58 . Again, these findings demonstrate that the regulation 479 of ATF3 is highly cell and context specific.…”
Section: Reverse Phase Protein Array 358mentioning
confidence: 98%